Pengaruh Good Corporate Governance Dan Corporate Social Responsibility Terhadap Profitabilitas Dan Competitive Advantage Perusahaan (Studi pada Perusahaan Food and Beverages yang terdaftar di Bursa Efek Indonesia dan Tahun 2014-2018) - Etica Aprillia; Hadiah Fitriyah (International Journal on Orange Technologies, 2021)
The research aim to examine the effect of good corporate governance and corporate social responsibility to the profitability and competitive advantage of the company with measured of the return on asset, return on equity, net profit margin. This research sample is food and beverages companys of registered in indonesia stock exchange to period 2014-2018. This research used quantitative approach with to collected data used dokumenter method and literature review. Sample selection used of the purposive sapling and obtained 7 companys in each period.This research used multiple regression analysis to analyze data. The research result showed good corporate governance and corporate social responsibility take effect positive and significant to the profitability and competitive advantage of the company.